Towards an ideal method of inoculation for screening sugarcane genotypes against red rot caused by Colletotrichum falcatum - and S.C. MISRA, S.K. DUTTAMAJUMDER* (Indian Phytopathology, 2004)
Assessment of relative performance of plug method, nodal method, and the proposed Parafilm method of red rot inoculation was made. Inoculations were carried out in both plug and nodal methods as suggested by the AICRP on Sugarcane. In the proposed Parafilm method, nodal maturity of cane stalk was taken as the guiding factor for inoculation. Thus, 5th or 6th node (the node up to which leaf sheath can be removed from the node without breaking/injuring the top) of the cane stalk from the 1st open leaf was taken for this purpose. After careful removal of the leaves, a sterile absorbent cotton swab (just sufficient to cover the node and easily holds 1 ml fluid) soaked in red rot inoculum (106 conidia/ml) was placed around the node and was sealed by wrapping Parafilm strip to prevent moisture loss. Immature nodes of the top catch more infection than the mature nodes at the bottom. The success of infection increased substantially, from the maximum 18 per cent in the nodal inoculations to the minimum 83 per cent in the Parafilm method. The Parafilm method excelled the standard plug method of inoculation with a consistent higher success rate of disease development. This method has the advantage of both nodal and plug method (placement of inoculum on the immature exposed node and advantage of superficial injury due to removal of leaf) and provides much more stable disease reaction for a longer period from July to November in comparison to both the prevalent methods.